2005
DOI: 10.1021/jo051766q
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric and Ratiometric Fluorescence Sensing of Fluoride:  Tuning Selectivity in Proton Transfer

Abstract: Phenyl-1H-anthra[1,2-d]imidazole-6,11-dione (1) and its derivatives (2 and 3) have been investigated as new colorimetric and ratiometric fluorescent chemosensors for fluoride. Acute spectral responses of 1 and 3 to fluoride in acetonitrile have been observed: an approximately 100 nm red shift in absorption and fluorescence emission and a very large ratiometric fluorescent response (R max /R min is 88 for sensor 1 and 548 for sensor 3). From the changes in the absorption, fluorescence, and 1 H NMR titration spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
201
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(208 citation statements)
references
References 37 publications
7
201
0
Order By: Relevance
“…Previous studies have revealed that a proton transfer (PT) in the ground state or an excited-state PT (ESPT) process via a hydrogen bond is often responsible for the colorimetric and fluorescent signaling of chemosensors. 15,16 However, in these studies it was not unequivocally established whether PT takes place in the ground state or the excited state. To further understand the mechanism, density functional theory (DFT) and time-dependent DFT (TD-DFT) could be used to clarify fundamental aspects concerning the different electronic states and structures.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have revealed that a proton transfer (PT) in the ground state or an excited-state PT (ESPT) process via a hydrogen bond is often responsible for the colorimetric and fluorescent signaling of chemosensors. 15,16 However, in these studies it was not unequivocally established whether PT takes place in the ground state or the excited state. To further understand the mechanism, density functional theory (DFT) and time-dependent DFT (TD-DFT) could be used to clarify fundamental aspects concerning the different electronic states and structures.…”
Section: Introductionmentioning
confidence: 97%
“…17 Hydrogen bonding is the most general and important interaction underpinning chemosensors designed to detect anions. 15,16,[18][19][20][21][22][23][24] A few chemosensors of them containing XÀ ÀH moieties (where X is an electronegative atom such as N or O) moieties enable selective anion recognition in aqueous solution. 18,19 It is noted that a p-system bearing an XÀ ÀH moiety may be an appropriate candidate for designing chemosensors for anions.…”
Section: Introductionmentioning
confidence: 99%
“…There are a series of ratiometric chemosensors for fluoride anion having been developed with the strategy that involves the hydrogenbonding interactions [12][13][14], the Lewis acid/base interactions [13,15,16] and the fluoride-triggered Si(B, C)-O cleavage reactions [1-3, 6, 17, 18]. Among these chemosensors, those with tert-butyldimethylsilyl and tert-butyldiphenylsilyl belong to the reaction-based type [2] and exhibit higher selectivity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the sensor-anion interactions are based on hydrogen bonding interaction and some of them are followed by sensor deprotonation [4][5][6]. Furthermore, the chemosensor sensing mechanisms have been suggested as intramolecular charge transfer (ICT) [7], photoinduced electron transfer (PET) [8], excited states proton transfer (ESPT) [9], and metal-ligand charge transfer (MLCT) [10]. Chalcone derivative, 3-(4-hydroxy-3-methoxy phenyl)-1-phenyl-2-propen-1-one (1), is promising candidate for anion chemosensor because of its ability for proton donating in hydrogen bonding interaction and its conjugation system through phenol ring and enone group [11][12].…”
Section: Introductionmentioning
confidence: 99%